(untitled) (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2025)
This study aims to analyze the effectiveness of using Student Worksheets (LKPD) in improving the learning independence and creativity of fifth-grade students in mathematics learning at State Elementary School 33 Pontianak Barat. This study employs a quantitative approach with a pre-experimental one-group pretest-posttest design. The research sample consisted of 28 fifth-grade students from class V-B. Data were collected through a learning independence questionnaire, creativity observation sheets, and learning achievement tests. The results of the normality test showed that all data were normally distributed (p > 0.05). Hypothesis testing using the Paired Samples t-test revealed a significance value (2-tailed) of 0.000 (p < 0.05) for learning independence, creativity, and learning outcomes, indicating that the improvement was statistically significant and not due to chance. The effect size for learning independence was 1.788 and for creativity was 1.802, both categorized as high. These high effect sizes suggest that the use of LKPD had a substantial and meaningful impact on students’ learning behavior, enhancing their ability to work independently, think creatively, and engage actively during lessons. Based on these findings, the use of LKPD is proven to be effective in improving students’ learning independence and creativity in mathematics learning, particularly on the topic of the perimeter of flat shapes. In practical terms, educators can implement LKPD-based learning strategies to promote self-directed and student-centered learning in various subjects, encouraging students to take greater responsibility for their learning while developing creative problem-solving skills